Pendampingan Sertifikasi Halal Self Declare Produk Telur Asin untuk Penguatan Daya Saing UMKM Desa Jatimulyo - Happy Surya Kurniawan; Nazwatul Ikna Auliani; Meilysa Anggita Hidayat; Neli Feliana Atmaja; Meilani Dwi Damayanti; Lorichika Gustinda Larasati (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Micro, small, and medium enterprise (MSMEs) processing salted eggs in Jatimulyo Village, Kuwarasan Subdistrict, Kebumen Regency, exhibit considerable economic potential stemming from straightforward production processes, locally accessible raw materials, and consistent market demand. Nevertheless, these enterprises encounter substantial obstacles, including limited comprehension of halal product assurance mechanisms, deficiencies in business legality documentation, and the lack of systematic production records, thereby constraining their competitiveness and expanded market penetration-particularly among consumers who increasingly demand verifiable halal assurance. This community services initiative sought to guide salted egg producers in securing halal certification via the self-declare pathway, thereby bolstering business legitimacy, consumer confidence, and the overall competitiveness of local products. Employing a participatory mentoring framework, the program encompassed eligibility assessment for self-declare suitability, facilitation of Business Identification Number (NIB) acquisition, interactive socialization on halal principles and regulation involving approximately 30 village participants, technical assistance in data submission and document uploading via the SiHalal platform, on site production process verification in collaboration with Halal Product Process Assistants (PPH), and formulation of self-declaration statements. The intervention yielded enhanced producer capacity to understand and satisfy halal certification prerequisites, successful attainment of NIB for formal business recognition, and improved preparedness for certification application. These advancements are anticipated to facilitate broader market outreach, elevate product value addition, and foster the long-term, self-reliant sustainability of village-rooted micro enterprises leveraging indigenous resources (Ilham, 2023).